1995
DOI: 10.1016/s0194-59989570316-0
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular neuritis

Abstract: Because the cause of vestibular neuritis is unknown, this disorder is best understood as a constellation of characteristic clinical symptoms and signs. The differential diagnosis includes peripheral otologic disorders, including Meniere's disease, perilymph fistula, and vestibular atelectasis; and central disorders, including vascular insufficiency, acoustic neuroma, migraine equivalent, paraneoplastic syndrome, metastatic carcinoma, and multiple sclerosis. The site of lesion, as evaluated by clinical signs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Radiological evidence for the pathologic condition within the inner ear in SSNHL‐V has been demonstrated, 30 and clinical findings suggesting end organ damage have been reported 31,32 . In VN, the pathologic site is believed to lie within the vestibular nerve, and degeneration of the vestibular nerve with or without vestibular hair cell damage has been observed in VN 33,34 . In contrast, the lesioned site of RHS‐V that is responsible for the vestibular deficit is still a subject of great controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological evidence for the pathologic condition within the inner ear in SSNHL‐V has been demonstrated, 30 and clinical findings suggesting end organ damage have been reported 31,32 . In VN, the pathologic site is believed to lie within the vestibular nerve, and degeneration of the vestibular nerve with or without vestibular hair cell damage has been observed in VN 33,34 . In contrast, the lesioned site of RHS‐V that is responsible for the vestibular deficit is still a subject of great controversy.…”
Section: Discussionmentioning
confidence: 99%
“…The superior vestibular nerve innervates the lateral semicircular canal crista, superior canal crista, macula utriculi, and dorsum of the macula sacculi. Nadol 15 has shown degeneration of the lateral canal crista in association with superior division vestibular neuritis. Neuritis could also affect the utricular nerve, thus removing otolith inhibition from the lateral semicircular canal efferents at the level of the vestibular nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…A viral etiology of AUVP is -in analogy to Bell's palsy and some types of acute hearing loss -likely but so far not proven [13,14,54,86,117,137]. There are several lines of evidence for such an etiology: a) a post-mortem study showed inflammatory degeneration of the vestibular nerve [136], b) demonstration of HSV-1, latency-associated transcripts in vestibular ganglia, and activated CD8 + T cells [3, 5-8, 68, 150].…”
Section: Etiologymentioning
confidence: 99%